Validity and reliability of anti-diabetic medication adherence scale among patients with diabetes in Baghdad, Iraq: a pilot study - Mohamed Azmi Hassali; Ehab Mudher Mikhael; Saad A Hussain; Nizar Shawky (BMJ Open Diabetes Research & Care)
Background Medication non-adherence is a common problem among patients with diabetes. Patient-reported medication adherence scales are the most commonly used method to assess patient medication adherence, but up to today there is no specific tool for assessing medication adherence among patients with diabetes in Arab countries. This study aimed to develop and validate a new tool for assessment of adherence to antidiabetic medications among Iraqi patients with diabetes.Methods The Iraqi Anti-Diabetic Medication Adherence Scale (IADMAS) consists of eight items. The face and content validity of the IADMAS were established via an expert panel. For convergent validity, the IADMAS was compared with the Medication Adherence Questionnaire (MAQ). For concurrent validity, the IADMAS was compared with glycosylated hemoglobin. A total of 84 patients with types 2 diabetes were recruited from a diabetes center in Baghdad, Iraq. Test–retest reliability was measured by readministering the IADMAS to the same patients 4 weeks later.Results Only 80 patients completed the study (response rate: 95%). Reliability analysis of the IADMAS showed a Cronbach’s alpha value of 0.712, whereas that of the MAQ was 0.649. All items in the IADMAS showed no significant difference in the test–retest analysis, indicating that the IADMAS has stable reliability. There was no difference in the psychometric properties of the IADMAS and the MAQ. The sensitivity and specificity of the IADMAS were higher than that of the MAQ (100% vs 87.5% and 33.9% vs 29.7%, respectively).Conclusion The IADMAS developed in this study is a reliable and valid instrument for assessing antidiabetic medication adherence among Iraqi patients.